75 IS CHRONIC HIGH-FREQUENCY GASTRIC ELECTRICAL STIMULATION EFFECTIVE IN PATIENTS WITH CHRONIC FUNCTIONAL NAUSEA AND VOMITING AND A NORMAL GASTRIC EMPTYING?. (1st January 2006) - Lin, Z.; Sarosiek, I.; Forster, J.; McCallum, R. W.
Abstract : The aim of this study was to investigate the effectiveness of high-frequency gastric electrical stimulation (GES, Enterra Therapy) in patients with symptoms suggestive of gastroparesis but who had a normal gastric emptying and were given the diagnosis of functional nausea and vomiting. Methods: This study included 11 such patients (3 M, 8 F, median age 41 years, range 21-53, 4 diabetic and 7 idiopathic) who had a documented normal baseline gastric emptying test (GET) (normal value at 4 hours < 10% gastric retention) and received GES therapy for at least 1 year. Patient characteristics, total symptom score (TSS) derived from 7 upper gastrointestinal symptom subscores (0-4), and 4-hour standardized GET using a low-fat egg meal were evaluated at baseline and at 1 year of GES, which was implanted and programmed according to our previous publications in gastroparesis patients (Am J Surg 2001;182:676-81). Data are presented as median (range). Results of 2-hour and 4-hour gastric retention (%) and nausea, vomiting scores and TSS and weight at baseline and 1 year of GES are summarized in the table below. Overall there was no significant change in gastric emptying and approximately 67% patients continued to have a normal GET after 1 year of GES. However, one-third of patients did develop a slowing of GET (> 10% retention at 4 hours). Symptom severity of nausea, vomiting, and TSS were significantly improved. Sixty-four percent of patients had 50% reduction in TSS and the median reduction of TSS was 51%. Patients overall maintained their weight during the GES therapy. Conclusions: In patients with functional nausea and vomiting and a normal GET high-frequency GES is effective in improving nausea, vomiting, and related symptoms as well as maintaining nutrition.